Improving Patient Safety in General Hospitals Using Structured Handoffs: Outcomes From a National Project - Toren, Orly; Lipschuetz, Michal; Lehmann, Arielle; Regev, Gil; Arad, Dana (Frontiers in Public Health, 2022)
Background Promoting quality and patient safety is one of the health policy pillars of Israel's Ministry of Health. Communication among healthcare professionals is of utmost importance and can be improved using a standardized, well-known handoff tool such as the Introduction, Situation, Background, Assessment, and Recommendations (ISBAR). This study aims to present implementation process and participants' satisfaction of a national project that used a standardized tool for team communication. Methods This national intervention project included process implementation teams from 17 Israeli general hospitals evaluating the ISBAR implementation process for transferring patients from intensive care units to medical/surgical wards. The project, conducted between January 2017 and March 2018, used Fischer's test and logistic regression. The project evaluation was based on the participants' assessment of and satisfaction with the handoff process. Results Eighty-seven process implementers completed the questionnaire. A statistically significant increase in satisfaction scores in terms of four variables (p < 0.001) was observed following the implementation of the project. Nurses reported higher satisfaction at the end of the process (0.036). Participants who perceived less missing information during handoffs were more satisfied with the process of information flow between wards (84.9%) than those who perceived more missing information (15.6%). Participants who responded that there was no need to improve information flow were more satisfied with the project information flow (95.6%) compared to the group which responded that it was necessary to improve information flow (58.2%). Three out of four variables predicted satisfaction with the process. Being a nurse also predicted satisfaction with information flow with a point estimate of 2.4. The C value of the total model was 0.87. Conclusions Implementation of a safety project at a national level requires careful planning and the close involvement of the participating teams. A standardized instrument, a well-defined process, and external controls to monitor and manage the project are essential for success. Disparities found in the responses of nurses vs. physicians suggest the need for a different approach for each profession in planning and executing a similar project in the future.